An ecosystem services approach to the ecological effects of salvage logging: valuation of seed dispersal. Issue 4 (22nd May 2017) - Leverkus, Alexandro B.; Castro, Jorge
Abstract: Forest disturbances diminish ecosystem services and boost disservices. Because post‐disturbance management intends to recover the greatest possible value, selling timber often prevails over other considerations. Ecological research has shown diverse effects of salvage logging, yet such research has focused on the biophysical component of post‐disturbance ecosystems and lacks the link with human well‐being. Here we bridge that gap under the ecosystem services framework by assessing the impact of post‐fire management on a non‐timber value. By employing the replacement cost method, we calculated the value of the post‐fire natural regeneration of Holm oaks in southern Spain under three post‐fire management options by considering the cost of planting instead. The value of this ecosystem service in non‐intervention areas doubled that of salvage‐logged stands due to the preference for standing dead trees by the main seed disperser. Still, most of the value resulted from the resprouting capacity of oaks. The value of this and other ecosystem services should be added to traditional cost/benefit analyses of post‐disturbance management. We thus call for a more holistic approach to salvage logging research, one that explicitly links ecological processes with human well‐being through ecosystem services, to better inform decision‐makers on the outcomes of post‐disturbance management.